Very high contrast IFU spectroscopy of AB Doradus C: 9 mag contrast at 0.2" without a coronagraph using spectral deconvolution - Thatte, N; Abuter, R; Tecza, M; Nielsen, E; Clarke, F; Close, L (2007)
We present an extension of the spectral deconvolution method (Sparks and Ford 2002) to achieve very high contrast at small inner working radii. We apply the method to the specific case of ground based adaptive optics fed integral field spectroscopy (without a coronagraph). Utilising the wavelength dependence of the Airy and speckle patterns, we make an accurate estimate of the PSF that can be scaled and subtracted from the data cube. The residual noise in the resulting spectra is very close to the photon noise from the starlight halo. We utilise the technique to extract a very high SNR H and K band spectrum of AB Dor C, the low mass companion to AB Dor A. By effectively eliminating all contamination from AB Dor A, the extracted spectrum retains both continuum and spectral features. The achieved 1 sigma contrast is 9 mag at 0.2", 11 mag at 0.5", in 20 mins exposure time, at an effective spectral bandwidth of 5.5 nm, proving that the method is applicable even in low Strehl regimes. The spectral deconvolution method clearly demonstrates the efficacy of image slicer based IFUs in achieving very high contrast imaging spectroscopy at small angular separations, validating their use as high contrast spectrographs/imagers for extreme adaptive optics systems.